Die Chloropidenfauna (Diptera, Chloropidae) immissionsgeschädigter Rasenbiotope im Saaletal bei Jena (Thür.). XV. Beitrag über den Einfluß von Luftverunreinigungen auf Ökosysteme. - Bährmann, Rudolf; Weipert, Jörg (Contributions to Entomology = Beiträge zur Entomologie, 1989)
The chloropids on a complex of five different lawn biotopes polluted to varying degrees by immissions from a fertilizer factory in the Saale valley near Jena were examined by means of netting, Barber traps and yellow bowl traps. The examinations were made in the years from 1978 to 1982 and in 1985. A total of 45529 chloropids belonging to 48 species were trapped. Of these, 13 are eurytopic, i. e. they were netted between 1978 and 1982 at least in one year in all test areas. This relatively high percentage of eurytopic species corresponds to relatively high Renkonen values of identity of dominants in comparison with the identity of dominants of chloropids on near-natural lawn biotopes. The representation - proportional distribution of the individuals of a species on all lawn biotopes examined - of the 12 species with the greatest number of individuals showed with few exceptions a more or less even distribution of individuals. The relations of species and individuals in test area 4 produced a relatively steep curve of dominance caused chiefly by the density of individuals of the highest-ranking species. A more even structure of dominance was evidenced by the test areas 1, 2, 3 and 5. The rate of fluctuation of species is higher for Agropyron lawn than for the other test areas. Among the relatively frequent chloropid species is Meromyza nigriventris, the seasonal forms of which were examined more closely. By checking the hatching of chloropid imagoes from Agropyron and Puccinellia samples taken monthly between March and August 1985 from the field into the laboratory, the relations of ten species to their host plants could be established or confirmed. From the results of the hatching checks combined with examinations of the egg development data could be obtained about the seasonal settling in ecological niches of the chloropid species with high numbers of individuals in the test areas 4 and 5. The majority of the species examined in this way will normally produce two generations per year. 16 of the 48 species appeared in at least one of the test areas in each of the years from 1978 to 1982 and thus persistently. The highest percentage of persistent species was found on Puccinellia lawn, the test area with the greatest pollution by immission. - The density of individuals of the different species can vary greatly from year to year. High numbers of individuals of potential agricultural pests among the chloropids, as the Oscinella species that are frequent in the region under consideration, constitute a latent threat to adjacent areas of cultivation. - The settling in ecological niches of the chloropid species of the immission area in space and time is compared with the space and time structure of the chloropids of near-natural lawn biotopes.